(untitled) (Swiss Medical Weekly, 2025)
AIMS: This study aims to provide age-specific prevalence of time spent on-screen among children and adolescents, to identify its sociodemographic and family-related determinants and to assess its impact on physical and psychosocial health outcomes. METHODS: Data was drawn from the SEROCoV-KIDS prospective cohort study, which includes randomly selected children living in Geneva, Switzerland. Daily screen time, sociodemographic and family characteristics were collected at baseline (December 2021 to June 2022). Physical and psychosocial health outcomes were measured at one-year follow-up. RESULTS: Among 674 children (2–8 years old), 752 preadolescents (9–13 years old) and 434 adolescents (14–17 years old), median daily screen time was 0h29, 1h14 and 3h18, respectively. Lower parental education and poorer parenting practices were associated with higher screen time in all age groups. In children only, poor parental mental health (+14 minutes/day; 95% CI: 2–27) and work-family conflicts (+6 minutes/day; 95% CI: 2–10) were related to increased screen time. After adjustment, elevated screen time was associated with an increased likelihood of poor physical-, emotional- and school-related quality of life in preadolescents and adolescents and of social difficulties in adolescents one year later. CONCLUSION: Almost all children engage with screens, but those from socially disadvantaged backgrounds and with strained families face a heightened risk of prolonged screen time. The health consequences we identified call for close monitoring.